1973
DOI: 10.1083/jcb.56.3.838
|View full text |Cite
|
Sign up to set email alerts
|

Radioautographic Visualization of the Deposition of a Phosphoprotein at the Mineralization Front in the Dentin of the Rat Incisor

Abstract: A peptide that is rich in organically bound phosphorus and contains abundant serine residues has been identified in the dentin of man (1), fetal bovine (2, 3), and rat (4). This phosphoprotein may play a role in mineralization (5-9). Butler et al. (4) reported that the phosphoprotein of rat incisor dentin constituted 10.8% of the proteinaceous material recovered from decalcified incisor teeth while collagen comprised 84%. Since the phosphorus content of the phosphoprotein was estimated at 3.29% and that of c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
122
0

Year Published

1976
1976
2012
2012

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 256 publications
(125 citation statements)
references
References 14 publications
3
122
0
Order By: Relevance
“…The findings may also be relevant to the role of phosphorylated components in mineralization of bone and dentin [26][27][28][29][30][31][32], since soluble and collagen-bound phosphorylated peptides of dentin and bone are rich in aspartic and glutamic acids [32][33][34][35] and calcium binding studies have indicated that some of the calcium ions are probably bound to collagen as a complex between carboxyl and phosphate groups [36].…”
Section: Discussionmentioning
confidence: 99%
“…The findings may also be relevant to the role of phosphorylated components in mineralization of bone and dentin [26][27][28][29][30][31][32], since soluble and collagen-bound phosphorylated peptides of dentin and bone are rich in aspartic and glutamic acids [32][33][34][35] and calcium binding studies have indicated that some of the calcium ions are probably bound to collagen as a complex between carboxyl and phosphate groups [36].…”
Section: Discussionmentioning
confidence: 99%
“…The first indication that phosphoproteins were indeed synthesized in mineralized tissues came from the elegant radioautographic studies of Weinstock and Leblond (10) vestigators followed the localization of 33P first in the odontoblasts and later at the mineralization front of the extracellular matrix ofthe dentin of rats injected with "Pi (inorganic orthophosphate).' Although the visualized radiolabel was not identified biochemically as being an integral component of a protein, the data were consistent with subsequent studies of Munksgaard et al (11), who demonstrated active biosynthesis of phosphoprotein by dentinal tissue in organ culture, and the in vivo biosynthesis studies of Dimuzio and Veis (12).…”
mentioning
confidence: 99%
“…After 4h of incubation in the presence of testosterone and dibutyryl cyclic AMP, 66 and 71 % of the tricWloroacetic acid-insoluble 32P appeared in the medium, the total secretion amounting to' 246 and 206 % respectively of the 370C controls ( (Singhal &; labelled components, as shown by the fact that 55 % 'Sutherland, 1975 We infer from the findings in the control slices that 32p1 must have been incorporated into secretory constituents shortly before the latter were packaged in secretory granules or lysosomes or both and released into the incubation medium. The phosphorylation of phosphoproteins of milk (the caseins) (Bingham et al, 1972) and tooth dentin (Weinstock & Leblond, 1973) is known to occur in the Golgi apparatus. It is therefore likely that the phosphorylation of secretory constituents in the seminal vesicle also takes place in the Golgi apparatus.…”
Section: Resultsmentioning
confidence: 99%